Cradling Cultures: A Comparative Study of Ethno-Parenting in Javanese and Korean Lullabies - Octavianisa, Icha Nur; Yulianeta, Yulianeta; Durachman, Memen (Makassar State University, 2025)
Abstract. Lullabies play an important role in transmitting cultural values and intergenerational affection. Its essence and practice are realized through ethnoparenting. However, this research is still relatively understudied, especially because it uses comparative analysis. Thru a comparison of the songs